ANALISIS PENYUSUNAN ANGGARAN BERBASIS KINERJA DINAS PENDAPATAN DAN PENGELOLAAN KEUANGAN KOTA SURABAYA - Kurniawan, Taufiq Pratama (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is to find out how the performance based budgeting is and what sort of problems to deal with. In order to find out and to analyze the performance based budgeting at Department of Revenue and Financial Management of Surabaya City has referred to the Regulation of Minister for Internal Affairs no 59 of 2007 which is related to budgeting system by using performance based budgeting is designed to create effectiveness and efficiency in the use of budget. The implementation activity of budgeting from 2011 to 2012 was carried out at Department of Revenue and Financial Management of Surabaya City had suitable with the determined responsibility. In budgeting realization report during 2011 to 2012 had not encountered any significant problem.Keywords: Budgeting, Performance, Efficiency, and Effectiveness